Hypertension in Saudi Arabia - Al-Nozha, Mansour M; Abdullah, Moheeb; Arafah, Mohammed R; Khalil, Mohamed Z; Khan, Nazeer B; Al-Mazrou, Yaqoub Y; Al-Maatouq, Mohammed A; Al-Marzouki, Khalid; Al-Khadra, Akram; Nouh, Mohammed S; Al-Harthi, Saad S; Al-Shahid, Maie S; et al. (Saudi medical journal, 2007)
To determine the prevalence of hypertension among Saudis of both gender, between the ages of 30-70 years in rural as well as urban communities. This work is part of a major national study on Coronary Artery Disease in Saudis Study (CADISS). This is a community-based study conducted by examining subjects in the age group of 30-70 years of selected households during a 5-year period between 1995 and 2000 in Saudi Arabia. Data were obtained from history using a validated questionnaire, and examination including measurement of blood pressure. The data were analyzed to provide prevalence of hypertension. Logistic regression was used to develop a risk assessment model for prevalence of hypertension. The total number of subjects included in the study was 17,230. The prevalence of hypertension was 26.1% in crude terms. For males, the prevalence of hypertension was 28.6%, while for females; the prevalence was significantly lower at 23.9% (p<0.001). The urban population showed significantly higher prevalence of hypertension of 27.9%, compared to rural population's prevalence of 22.4% (p<0.001). The prevalence of CAD among hypertensive patients was 8.2%, and 4.5% among normotensive subjects (p<0.001). Increasing weight showed significant increase in prevalence of hypertension in a linear relationship. Hypertension is increasing in prevalence in KSA affecting more than one fourth of the adult Saudi population. We recommend aggressive management of hypertension as well as screening of adults for hypertension early to prevent its damaging consequences if left untreated. Public health awareness of simple measures, such as low salt diet, exercise, and avoiding obesity, to maintain normal arterial blood pressure need to be implemented by health care providers.